Penerapan Penanaman Akhlak dalam Pembelajaran Tatap Muka (PTM) Terbatas di Pondok Pesantren Tahfidzul Qur'an - Azhari, Pebri; Khasanah, Uswatun; Hidayat, H. M. Yunan (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
This research is motivated by the problems of educational institutions in general which are related to how to be most effective in educating and teaching students through the Limited Face-to-face Learning system, especially related to instilling morals in students in Islamic boarding schools labeled tahfidz quran. Education in Islamic boarding schools, as is generally known, is carried out without any restrictions on the number or place. So the purpose of this study is to find out how the implementation of moral inculcation in face-to-face learning is limited in the tahfidzul quran Islamic boarding school and what are the supporting and inhibiting factors in its implementation. This study uses a qualitative research method with a case study approach. The data collection techniques used in this study were observation and interviews, while the data analysis model used was data reduction and conclusion drawing. Sources of data from this study are the teachers and staff of the Islamic boarding school imtaq shighor Isykarima. Researchers found that in previous research, research was conducted in non-dormitory-based educational institutions. Then in another study explaining the effects of limited face-to-face learning requires the school to use learning that uses video. So the difference between this research and previous research is how Islamic boarding school-based educational institutions in dealing with face-to-face learning are limited and learning still requires meeting teachers with students.